Effectiveness of the Contours Vibes™ soothing vibrations infant and toddler crib mattress on infant and maternal sleep quality and health outcomes: an intervention study - Hausenblas, Heather; Hooper, Stephanie (Sleep Science, 2022)
Objectives The purpose was to examine the effectiveness of the Contours Vibes™ Crib Mattress on infants’ and maternal sleep quality and health.Material and Methods Participants were 24 mothers and their infants. For Week 1 the infants slept on their current mattress (Baseline). For Week 2 they slept on the Vibrating Mattress without using the vibrating feature (VMC). For Week 3 they slept on the Vibrating Mattress using the vibrating feature (VMA). Sleep quality and health assessments were completed at Baseline and following VMA and VMC conditions.Results Sleep quality and health outcomes improved significantly for VMA compared to Baseline and VMC. VMC had significant improvements in some sleep and health outcomes compared to Baseline. No adverse events were reported.Conclusion The mattress is a simple, noninvasive, and non-pharmacological intervention that improved infant and maternal sleep quality and health. Further research is need examining the longitudinal effects of the mattress.
Keywords: Health; Infant; Sleep